2022
DOI: 10.3389/fcell.2022.1001954
|View full text |Cite
|
Sign up to set email alerts
|

Potential diagnostic of lymph node metastasis and prognostic values of TM4SFs in papillary thyroid carcinoma patients

Abstract: Background: Although the prognosis of papillary thyroid carcinoma (PTC) is relatively good, it causes around 41,000 deaths per year, which is likely related to recurrence and metastasis. Lymph node metastasis (LNM) is an important indicator of PTC recurrence and transmembrane 4 superfamily (TM4SF) proteins regulate metastasis by modulating cell adhesion, migration, tissue differentiation, and tumor invasion. However, the diagnostic and prognostic values of TM4SF in PTC remain unclear.Methods: This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Numerous studies have reported that TM4SF family members play a crucial role in many kinds of cancer [22][23][24]. However, their biological roles and prognostic value in LIHC have rarely been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that TM4SF family members play a crucial role in many kinds of cancer [22][23][24]. However, their biological roles and prognostic value in LIHC have rarely been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…TM4SF4 (transmembrane 4 superfamily 4) is a transmembrane protein that is regarded as a regulator of pancreas development (Anderson et al, 2011). TM4SF4 is associated with the prognosis of colorectal cancer (Huang et al, 2012), lung cancer (Choi et al, 2017), thyroid cancer (Wang et al, 2022) and liver cancer (Tang et al, 2024). Previous studies have shown that TM4SF4 is only highly expressed in a few cases of BC patients, however knocking down TM4SF4 can inhibit the growth of BC cells (Jung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Identi cation of speci c biomarkers related to PTC metastasis had been highly feasible due to high-throughput sequencing and bioinformatics technology development and several studies have screened gene signatures predicting the LNM of PTC. Kun Wang et al systematically evaluated the expression and potential mechanisms of transmembrane 4 superfamily (TM4SF) and revealed that a ve-gene prognostic model involved in TM4SFs could assess PTC progression effectively (Wang et al 2022). Yang Yu et al established a three hub-gene model including PTGS, MET and ICAM1 from immunerelated genes (IRGs) by LASSO and Random Forest method and validated those signature immune genes had potential functions for lymphatic metastasis in papillary thyroid cancer (Yu et al 2023) .…”
Section: Introductionmentioning
confidence: 99%